Systemic analysis of the 2013 Genting Highlands bus crash using the driver reliability and error analysis method (DREAM) - Syed Jamaludin, Muhammad Shaqif; Taib, Ibrahim Adham; Salleh, Azir (Malaysian Institute of Road Safety Research (MIROS), 2015)
The 2013 Genting Highlands Bus Crash that occurred on 21st August 2013 is widely regarded as the worst fatal road crash in Malaysia where 37 lives, including the driver, were lost. Based on a report produced by an independent advisory panel on the Genting Crash, an in-depth accident analysis method known as the Driving Reliability and Error Analysis Method (DREAM) was utilised to systematically analyse the contributing factors of the Genting Crash so that the cause of the accident can be explained according to systems thinking. The analysis indicated that the Genting Crash was not solely the fault of the driver but also the interaction between organisational, vehicle, and environmental factors. Although commonly used in Europe, there is little evidence that DREAM had been used in Malaysia. This study not only demonstrates the potential application of DREAM for analysing and preventing road traffic accidents in Malaysia but also suggests the modification of the tool for local context.